Green Accounting: Analisis Penerapan Green Innovation Pada Pengelolaan Limbah Pabrik Tahu di Kartasura - Nur Afra Hana Annisa Putri; Alviani Indraswari; Yahya Wulandari; Ronnawan Juniatmoko (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2022)
The tofu industry is currently expanding in Indonesia, especially in Purwogondo Village, Kartasura District. In the village, the majority of the population produces tofu. Tofu production is still carried out using traditional and simple technology. This causes the level of efficiency in the use of water and raw materials is still low but the level of waste production is also relatively high. Based on the research that has been done, the human resources involved or the workers in the tofu factory in the village generally have a relatively low level of education, so that not many workers and the tofu industry themselves do waste treatment properly. This research was conducted at the Tofu Factory of Mr. Parji which is one of the tofu factories in Purwogondo Village, Kartasura District, the study aims to analyze how the application of green accounting through the concept of green innovation in the waste management of Mr. Parji's tofu factory. The research method used is descriptive qualitative, namely by means of observation, direct interviews with relevant informants and documentation studies in the form of pictures. The results obtained from the research that have been carried out show that the application of green innovation to the waste of Mr. Parji's tofu factory has been carried out but has not been maximized. Applications that have been made in the form of solid waste tofu dregs are resold for animal feed or used alone, so that this will have a positive impact on the factory in the form of additional income and the impact on the surrounding environment will not be polluted. As for the liquid waste from the tofu factory, it is left in a shelter so that it just flows into the river.